Process Of Housing Transformation In Iran - Mirmoghtadaee, Mahta (Penerbit Universiti Sains Malaysia, 2009)
Iranian houses have changed dramatically in recent decades. The changes took place in three different periods in which social, economic, and technological transformations caused physical and morphological changes. This paper discusses the process of change analytically, emphasising the importance of compatibility between the house form and lifestyle. The spatial characteristics of traditional Iranian houses reflect natural, geographical, and cultural needs. There was a harmony between people’s needs and the physical characteristics of the house. In the transition period, however, a new residential type appeared, in which living spaces were categorised according to their general functions. Spatial arrangement, together with plan layout and proportions, facilitated the limited potential for varied lifestyles. In the contemporary period, apartment buildings became prevalent. In this new type of residence, the physical characteristics of the house have changed considerably, while living habits and lifestyles have not changed at the same pace. This paper concludes that habitats should be physically harmonious with traditions and lifestyles; otherwise, residents would react and try to change the environment according to their wishes. When the environment itself is not changeable, residents have to adapt themselves to their new conditions; consequently, some valuable traditions would be lost forever